Correlation between Marital Status and Consistent Use of Condoms in People with HIV (ODHIV) at Rumah Singgah Dukungan Sebaya Kota Gorontalo - Ilham, Rosmin; Rahim, Nirwanto; Sulistiani, Ita; Soeli, Yuniar M.; Husain, Filsa (PT.Mantaya Idea Batara, 2023)
HIV is still a major health problem, due to its increasing prevalence. To prevent it, many things can be done, one of which is the use of condoms. However, often the use of condoms is something that is often neglected so condoms are often inconsistent. The results of the study show that there is a significant relationship between marital status and the consistency of condom use. Married respondents tend to consistently use condoms. This is because married couples with status as PLWHA will pay more attention to safety in intercourse. After all, they realize that having intercourse without using a condom will worsen the partner's health condition. the significant relationship between marital status and consistency condoms